Socioeconomic Factors And Participation Of KB Suku Bajo Jaya Bakti Village, Pagimana Distritrict Banggai County Town, Central Sulawesi Province - Syamsuddin HM (PT. Publikasiku Academic Solution, 2023)
This study aims to analyze the relationship of faktor sosial economy with the partition of the KB pasi of the Bajo Tribe community, what factors cause the Bajo Tribe to still survive together in several heads of families in one house in Jaya Bakti Village. The sample determination method uses purposive sampling. snowball sampling. The statistical analysis method used is descriptive analysis followed by cross-tabulation analysis and Chi-Square. The results showed that the average education of this study sample was mostly (67,3,1%) educated in elementary school. From the income aspect of 74 respondents, 35 respondents or 47.4% belonged to the poor group. Most of the research samples worked as fishermen.There was a relationship between income and the use of contraceptives for married couples in research in the Bajo Tribe.